Uniform single atomic Cu1-C4 sites anchored in graphdiyne for hydroxylation of benzene to phenol - Yu, Jia; Cao, Changyan; Jin, Hongqiang; Chen, Weiming; Shen, Qikai; Li, Peipei; Zheng, Lirong; He, Feng; Song, Weiguo; Li, Yuliang (National science review, 2022)
For single-atom catalysts (SACs), the catalyst supports are not only anchors for single atoms, but also modulators for geometric and electronic structures, which determine their catalytic performance. Selecting an appropriate support to prepare SACs with uniform coordination environments is critical for achieving optimal performance and clarifying the relationship between the structure and the property of SACs. Approaching such a goal is still a significant challenge. Taking advantage of the strong d-π interaction between Cu atoms and diacetylenic in a graphdiyne (GDY) support, we present an efficient and simple strategy for fabricating Cu single atoms anchored on GDY (Cu1/GDY) with uniform Cu1-C4 single sites under mild conditions. The Cu atomic structure was confirmed by combining synchrotron radiation X-ray absorption spectroscopy, X-ray photoelectron spectroscopy and density functional theory (DFT) calculations. The as-prepared Cu1/GDY exhibits much higher activity than state-of-the-art SACs in direct benzene oxidation to phenol with H2O2 reaction, with turnover frequency values of 251 h−1 at room temperature and 1889 h−1 at 60°C, respectively. Furthermore, even with a high benzene conversion of 86%, high phenol selectivity (96%) is maintained, which can be ascribed to the hydrophobic and oleophyllic surface nature of Cu1/GDY for benzene adsorption and phenol desorption. Both experiments and DFT calculations indicate that Cu1-C4 single sites are more effective at activating H2O2 to form Cu=O bonds, which are important active intermediates for benzene oxidation to phenol.